Perbedaan disposisi matematika siswa yang mengikuti kursus dan tidak mengikuti kursus: mana yang lebih baik? - Andi Gusmaulia Eka Putri; Rian Priyadi; Khoirunnisa Khoirunnisa (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to describe the mathematical disposition of junior high school students who course attendance and who non-course attendance outside school. The subjects in this study were 24 junior high school students in Yogyakarta consisting of 12 students who course attendance and 12 students who non-course attendance. This study uses a qualitative descriptive design, which describes the data on the results of students' mathematical disposition responses based on data collected through a likert scale questionnaire prepared based on seven indicators of mathematical disposition according to the NCTM, there are 31 statement items in this study. The results showed that the mathematical disposition of junior high school students who course attendance and those who non-course attendance outside school hours was still relatively low. The average achievement of mathematical disposition indicators of students who participated in out-of-school course in this research subject only fulfilled 69.6% while students who did not participate in out-of-school course in this research subject only fulfilled 62.1% of the expected percentage.